2015
DOI: 10.1212/wnl.0000000000002062
|View full text |Cite
|
Sign up to set email alerts
|

Temporal anteroinferior encephalocele

Abstract: The possibility of a temporal encephalocele should be considered when interpreting MRI examinations of patients with medically intractable focal epilepsy. These patients can significantly benefit from unitemporal epilepsy surgery, even in cases with bilateral encephaloceles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 29 publications
1
55
1
2
Order By: Relevance
“…Patients with TEs were more likely to have temporalonset seizures on scalp EEG, and although statistical significance for patients with intracranial EEG was not achieved due to a lack of power for this comparison, all patients with TEs for whom seizures were recorded had seizures localized as temporal-onset. Although the prevalence of TEs in patients referred to tertiary centers for epilepsy has been reported as 2%-4%, 15,16 we found that 12.5% of patients referred to our refractory epilepsy conference were diagnosed with TEs after careful systematic review of MR imaging with special attention paid to the anterior temporal lobes. We found that TEs were often overlooked on initial review and that patients with TEs were likely to have prior imaging findings that were normal, similar to findings in other smaller studies.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Patients with TEs were more likely to have temporalonset seizures on scalp EEG, and although statistical significance for patients with intracranial EEG was not achieved due to a lack of power for this comparison, all patients with TEs for whom seizures were recorded had seizures localized as temporal-onset. Although the prevalence of TEs in patients referred to tertiary centers for epilepsy has been reported as 2%-4%, 15,16 we found that 12.5% of patients referred to our refractory epilepsy conference were diagnosed with TEs after careful systematic review of MR imaging with special attention paid to the anterior temporal lobes. We found that TEs were often overlooked on initial review and that patients with TEs were likely to have prior imaging findings that were normal, similar to findings in other smaller studies.…”
Section: Discussionmentioning
confidence: 67%
“…[5][6][7][8][9][10][11][12] Since that time, a recent increase in cases of TEs in patients with refractory epilepsy has been observed. [13][14][15][16][17] The prevalence of TEs among the largest case series has been 2%-4% of drug-resistant patients referred for epilepsy surgery evaluation, and TEs have been present in nearly 10% of patients with refractory temporal lobe epilepsy (RTLE), which have also accounted for 10% of surgical resections at some institutions. 15,16 Furthermore, it has been previously reported that 16%-31% of pa-tients with RTLE do not have a clearly identified lesion on routine MR imaging, 18,19 and TEs have been observed more frequently in patients with RTLE who had previously normal MR imaging findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Из всех возможных причин фармакорезистентной эпилепсии энцефалоцеле -одна из редких. В литературе описано около 45 таких случаев [3][4][5][8][9][10][11], в подавляющем большинстве которых хирургическое лечение оказалось эффективным.…”
Section: Discussionunclassified
“…Продолжается дискуссия по поводу объема резекции ткани мозга, однако многие авторы сходятся на том, что достаточной является резекция энцефалоцеле с прилегающими 1-1,5 см 3 ткани мозга [3][4][5]12]. Предполагается, что поводом для расширения объема резекции могут быть данные нейровизуализации, указывающие на морфологические изме-нения комплекса амигдала-гиппокамп, или быстрое распространение эпилептиформной активности на данную область по результатам ЭЭГ [7,13].…”
Section: Discussionunclassified